(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The objective of the research was to evaluate consumer purchasing behavior through the Internet, such as consumer behavior, reasons for buying online, purchasing advantages over the Internet, personal variables (gender, age, marital status, education level, income, and income and job type). The questionnaire was adopted as a main tool in the survey of the views of a sample of consumers in Baghdad governorate (100) people and analyzed their answers using the statistical program SPSS in calculating the mean and standard deviation Centigrade, correlation coefficient (R) and test ( ). The main findings of the research were: • There is a positive and positive relationship between consumer purchasing behavior via the Internet and personal variables. 2. There are significant differences in the responses of the selected sample according to the personal variables (social status, education level, income, income type, job)